A patrulha escolar comunitária (PEC) como expressão da política de segurança pública brasileira da crise estrutural do capital - Castro, Cátia Ronsani (2013)
This dissertation is the result of studies that developed about a problem that has disquieted in the professional workspace and union militancy: the extent of the actions of the military police to schools as a policy of Public Security of the State of Paraná. With the research presented elements that aim to understand why the police has constituted effectively as the main public policy of the State of Paraná to deal with violence in schools. We argue that the adoption of measures such as policing school, situated in the area of Public Security, is related to a broader movement of contemporary capitalist society, and expressed elements of Brazilian singularity. In the first chapter we explicit how the Criminal State is configured as an alternative to the crisis of the states of Welfare, especially as regards the implementation of a set of punitive policies in the area of Public Security, in exchange for social policies. In the second chapter, through an overview of the security situation in Brazil and the mistakes of the actions implemented by the State, since 1988, we outlined a framework of crisis Policy Public Safety. Crisis that establishes precisely the policies with contributions progressives have succumbed to the ruling military, inherited from the dictatorship period and also for the implications of the emergence of the Criminal State. In the last chapter, we present the Patrol School Community (PEC) and resumed elements of the first and second chapter to argue for this policy as Paraná is an expression of the crisis of the Brazilian Public Safety, in that it locally reproduces the movements that make the crisis nationwide: the failure of security policies with contributions and progressive expansion of policing and repression in order to address the demands of the social question. From these elements we have presented, we believe that a model of state facing social demands with the expansion of political repression and punishment, could not present this alternative way to address the problem of school violence